SrZnGeS4: A Dual‐Waveband Nonlinear Optical Material with a Transparency Spanning UV/Vis and Far‐IR Spectral Regions - Liu, Qian‐Qian; Liu, Xin; Wu, Li‐Ming; Chen, Ling (Angewandte Chemie International Edition, 2022)
Non‐linear optical chalcogenides with a wide band gap (Eg) and excellent NLO properties are key materials for highly desirable multiwaveband tunable optical parametric oscillators (OPOs). We exploit the “electronic structure engineer bucket effect” to develop a novel dual‐waveband SrZnGeS4 with an ultrawide transparency window. It exhibits an asymmetric Fdd2 structure that consists of layers formed by corner‐sharing [ZnGeS6] dimers. SrZnGeS4 is transparent from 0.30 to 23.6 μm, spanning the UV‐, vis‐, mid‐ and far‐IR spectral regions and has the widest Eg (3.63 eV) in the AeMIIMIVQ4 family to date. It exhibits phase matching, high SHG intensities (e.g., 11.0×KDP and 17.5×AGS under λinc=1450 and 950 nm, respectively), and a very high laser‐induced damage threshold (35×AGS). These results not only suggest bright prospects for high‐power laser applications but may also enable applications of the multiwaveband OPO system from the UV‐visible to far‐IR regions. An electronic structure‐engineering “bucket effect” strategy produces a novel non‐linear optical compound SrZnGeS4 with unique dual‐waveband NLO properties, including a second harmonic generation of 0.9–17.5×AgGaS2 under 850–2100 nm incident laser wavelengths and a laser‐induced damage threshold of 35×AgGaS2.